Pulsar polarimetry with the Parkes ultra-wideband receiver - Oswald, L; Karastergiou, A; Johnston, S (Oxford University Press, 2020)
Pulsar radio emission and its polarization are observed to evolvewith frequency. This frequency dependence is key to the emission mechanism and the structure of the radio beam.With the new ultra-wideband receiver (UWL) on the Parkes radio telescope we are able, for the first time, to observe how pulsar profiles evolve over a broad continuous bandwidth of 700-4000 MHz.We describe here a technique for processing broad-band polarimetric observations to establish a meaningful alignment and visualize the data across the band.We apply this to observations of PSRs J1056-6258 and J1359-6038, chosen due to previously unresolved questions about the frequency evolution of their emission. Application of our technique reveals that it is possible to align the polarization position angle (PA) across a broad frequency range when constrained to applying only corrections for dispersion and Faraday rotation to do so. However, this does not correspond to aligned intensity profiles for these two sources. We find that it is possible to convert these misalignments into emission height range estimates that are consistent with published and simulated values, suggesting that they can be attributed to relativistic effects in the magnetosphere. We discuss this work in the context of the radio beam structure and prepare the ground for a wider study of pulsar emission using broad-band polarimetric data.